Current status and recommendations for the fruit tree industry in east China's Jiangsu Province - Jialiang Kan; Mingliang Yu; Xiaogang Li; Mizhen Zhao; Yushan Qiao; Xicheng Wang; Jinlong Han; Yong Yang; Meng Wei; Zhijun Shen (Technology in Horticulture)
Jiangsu is a province with rich varieties and resources of fruit trees and advanced economic development in East China. To gain a deeper understanding of the current situation of fruit industry development in Jiangsu, a systematic survey was conducted on the current situation and technological needs of the fruit industry. The present article provides a detailed analysis of the distribution of fruit tree species, technological application, planting costs, and marketing models of fruit trees in Jiangsu, and points out the problems in regional layout, mechanized application, green production, and plantlet breeding. In addition, the present article also puts forward suggestions on strengthening the protection of germplasm resources, improving the level of mechanization and plantlet breeding system. Based on the results, we hope to provide scientific decision-making data support for the fruit industry in Jiangsu and to provide reference for the high-quality development of other fruit tree planting areas.